2012
DOI: 10.4236/jcpt.2012.24020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance Research of CuInSe<sub>2</sub> Materials Applied in Solar Cell

Abstract: At present, CuInSe 2 (referred to as CIS) semiconductor has become one of the hot points in solar cell field at home and abroad for its excellent performances, such as direct bandgap, high light absorption coefficient, high photoelectric conversion efficiency and long-term stability. In this paper, the CIS bulk materials are prepared by the horizontal Bridgman method with double-heat sources, the crystal structure, microstructure morphology and composition of the samples are analyzed in X-ray diffraction instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The conversion of molecular metal-chalcogenolate complexes and small clusters has proven to be a highly effective method for the formation of metal-chalcogenide extended solids, thin films, as well as nanoscale materials. ,, This includes works by Williams et al (photolysis) and Castro et al and Banger et al (thermolysis), who have demonstrated that the mixed-metal [(Ph 3 P) 2 ­CuIn­(ER) 4 ] (E = S, Se) can be used as molecular precursors to the related ternary nanomaterials CuInE 2 , taking advantage of the well-defined Cu:In:S ratio. Indeed, Castro and co-workers investigated in detail their decomposition to tetragonal CuInS 2 in noncoordinating, high boiling solvents where size selective preparation was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of molecular metal-chalcogenolate complexes and small clusters has proven to be a highly effective method for the formation of metal-chalcogenide extended solids, thin films, as well as nanoscale materials. ,, This includes works by Williams et al (photolysis) and Castro et al and Banger et al (thermolysis), who have demonstrated that the mixed-metal [(Ph 3 P) 2 ­CuIn­(ER) 4 ] (E = S, Se) can be used as molecular precursors to the related ternary nanomaterials CuInE 2 , taking advantage of the well-defined Cu:In:S ratio. Indeed, Castro and co-workers investigated in detail their decomposition to tetragonal CuInS 2 in noncoordinating, high boiling solvents where size selective preparation was achieved.…”
Section: Resultsmentioning
confidence: 99%